2018
DOI: 10.1108/jfmpc-03-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

The trickle-down effect of psycho-social constructs and knowledge deficiencies as organizational barriers to cost performance on highway projects

Abstract: The study aims to proffers a theoretical narrative explaining the poor financial performance of public highway agencies in Nigeria. This study critically spotlights seminal works in the literature offering theoretical narratives on the poor financial performance of public infrastructure projects, as to discuss whether they adequately capture the relationship between the psychological factors, project governance/leadership issues, ands well as knowledge/skill deficiencies related to the cost performance of infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…suitable data source and collection technique (Bryman and Bell, 2015). This is also in line with the recommendation of Amadi and Higham (2018) that, it is very vital to take a more contextually embedded view to have a broader understanding of the complex web of issues that are responsible for cost overrun in highway infrastructure projects. From the aforementioned, the study adopted a qualitative case study approach.…”
Section: Causes Of Cost Overrunsupporting
confidence: 76%
See 1 more Smart Citation
“…suitable data source and collection technique (Bryman and Bell, 2015). This is also in line with the recommendation of Amadi and Higham (2018) that, it is very vital to take a more contextually embedded view to have a broader understanding of the complex web of issues that are responsible for cost overrun in highway infrastructure projects. From the aforementioned, the study adopted a qualitative case study approach.…”
Section: Causes Of Cost Overrunsupporting
confidence: 76%
“…In all, 16 stakeholders across the 3 key organisations were interviewed for the study with experiences ranging from 10 years to more than 20 years. Though the issue of representation in field-oriented research is still debated Steinberg (2010) and Baker and Edwards (2012), this sample is, thus, considered a fair representation considering other studies from similar context Amadi and Higham (2018) and Amadi and Higham (2017) and also by considering the experience, knowledge of the contextual issues and geographical location of the participants (Kolb, 2008). Furthermore, in line with the recommendation of Guest et al (2006), data saturation can occur within the first 12 interviews after which few new phenomena are likely to emerge.…”
Section: Data Collectionmentioning
confidence: 99%
“…Like Curry et al (2011), the answers to these research questions were found to be rooted in political/project governance issues, that trickled down to the individual organizational practices of the highway agencies (Figure 8). Whereby psycho-social constructs and knowledge deficiencies acted as organizational barriers to cost performance on the highway projects (Amadi and Higham, 2018b).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The purpose of the interview was to explore vital and useful information from project stakeholders involved in highway construction projects on their perception and understanding of problematic issues related to cost overrun that is specific to the context of the study. Though the issue of representation in field oriented research is still debated Steinberg (2010) and Baker and Edwards (2012), this sample is thus considered a fair representation considering other studies from similar context Amadi and Higham (2018) and Amadi and Higham (2017) and also by considering the experience, knowledge of the contextual issues and geographical location of the participants (Kolb, 2008). In the second stage, 9 interviews with some stakeholders, as illustrated in Table 2, who participated in the first stage interview were conducted to validate the CLDs and the underlying conceptual thinking as suggested by Rwashana et al (2014).…”
Section: Methodsmentioning
confidence: 99%